Integrasi Pembelajaran Berbasis Masalah di SMA Negeri Palangka Raya dan Minat Belajar Siswa pada Pembelajaran PAK Remaja - Lukas, Lukas; Simon, Bernandus Louis (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Christian religious education has a significant role in shaping students' character and morality, but the challenges faced in increasing students' interest in learning are often the focus of attention. In an effort to overcome this, recent research has highlighted the importance of choosing effective learning models in increasing students' interest in learning in Christian Religious Education subjects. Choosing the right learning model can play a key role in stimulating students' interest in learning, because it not only teaches subject matter, but also creates an interesting and relevant learning environment. Educators need to consider various learning models that are appropriate to the learning theme in order to increase student interest and involvement. A learning approach that is interesting and relevant to students' needs can help motivate them to learn better